Strategi Komunikasi Dan Informatika Dalam Meningkatkan Kebutuhan Masyarakat Terhadap Berita Melalui Aplikasi Simata Sumsel - Cahaya, Anggi; Nuraida; Yahya, Ahmad Harun (CV. ITTC INDONESIA, 2023)
The background is a comprehensive application which summarizes various information and data such as the efforts made by the South Sumatra Provincial Government for regional and community progress, population and employment, agriculture, plantations, population, as well as detailed information regarding the condition of South Sumatra. So this research analyzes